A Comparative Study of the Resurrection of Jesus Christ and Taoist Immortals' Corpse Transformation - BI, Congcong; HUANG, Wei (Journal of Research for Christianity in China (JRCC), 2025)
The resurrection of Jesus Christ and the Taoist immortals' corpse transformation are both sacred religious events transcending conventional notions of death and supernatural narratives. Rooted in Greek tradition, the concept of Christ's resurrection and the corpse transformation alchemy originating from the Qin and Han dynasties described the aesthetics of bodily death through anti-soul transcendence almost simultaneously. Both Jesus as Christ and Taoist immortals appear as transcendent beings, achieving renewal of life forms through the transformation of physical bodies. The theological significance of Jesus' resurrection is reinforced within systematic theology, while the immortals' corpse transformation also reveals its theological practicality and philosophical essence of life. Resurrection and corpse transformation, both grounded in concepts of death, undoubtedly offer us a sacred and transcendent perspective on life.